Endogenous 17β-estradiol is required for activity-dependent long-term potentiation in the striatum: interaction with the dopaminergic system - Tozzi, Alessandro; de Iure, Antonio; Tantucci, Michela; Durante, Valentina; Quiroga-Varela, Ana; Giampà, Carmela; Di Mauro, Michela; Mazzocchetti, Petra; Costa, Cinzia; Di Filippo, Massimiliano; Grassi, Silvarosa; Pettorossi, Vito Enrico; et al. (Frontiers in Cellular Neuroscience, 2015)
17β-estradiol (E2), a neurosteroid synthesized by P450-aromatase (ARO), modulates various brain functions. We characterized the role of the locally synthesized E2 on striatal long-term synaptic plasticity and explored possible interactions between E2 receptors (ERs) and dopamine (DA) receptors in the dorsal striatum of adult male rats. Inhibition of E2 synthesis or antagonism of ERs prevented the induction of long-term potentiation (LTP) in both medium spiny neurons (MSNs) and cholinergic interneurons (ChIs). Activation of a D1-like DA receptor/cAMP/PKA-dependent pathway restored LTP. In MSNs exogenous E2 reversed the effect of ARO inhibition. Also antagonism of M1 muscarinic receptors prevented the D1-like receptor-mediated restoration of LTP confirming a role for ChIs in controlling the E2-mediated LTP of MSNs. A novel striatal interaction, occurring between ERs and D1-like receptors in both MSNs and ChIs, might be critical to regulate basal ganglia physiology and to compensate synaptic alterations in Parkinson's disease.